Water Quality Variation of Rewalsar Lake, Mandi District (H.P.), India - Supriya, Kalyani; Thakur, Sarita; Thakur, Nitasha; Aggarwal, R. K. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted from March, 2020 to February, 2023 to examine the ecological health of Rewalsar lake at Mandi district of Himachal Pradesh. In order to determine the fluctuations in the lake's water quality and to determine the factors that contributed to these variations in three distinct seasons-the post-monsoon, monsoon and pre-monsoon in the selected study area was conducted. There were thirteen physio-chemical and biological water quality parameters-pH, temperature, turbidity, TDS, DO, BOD, COD, Ca, Mg, Cl, Fl, Ni, and total coliform were evaluated. In the 2020–2021 rainy season, the computed water quality index peaked at 108.3854, followed by the summer season (57.5606) and the winter season (50.4625). The water quality index was highest during the rainy season (191.6324) in 2021–2022, followed by the summer season (114.6108) and the winter season (61.4355). Following analysis, the water quality index for the winter of 2022–2023 was 65.5439. The lake's computed water quality index was found to be at a moderate level, indicating that the water was unfit for domestic use and drinking. This was because of nearby construction and demolition, improper waste management, and an increase in pollution due to a lack of sustainable tourism development. It was discovered that the water quality was low and unfit for human consumption. The current study made management recommendations for Rewalsar town, including implementing an efficient waste management strategy, conducting routine environmental monitoring, and encouraging sustainable tourism.